Historical Development of University Education in Nigeria and Strategies for Sustainable Development - Sarkinfada, Halima; Simon Omoregie Ajayi (Researchparks Publishing, 2023)
This paper examined the historical development of university education in Nigeria and suggested strategies for sustainable development. Also, the paper looked at current challenges facing the Nigerian universities system. Secondary data were employed in the paper. The secondary data were collected from print and online publications. The paper made some useful suggestions for the sustainable development of university education in Nigeria.